Character Education Values in Ustadz Hanan Attaki’s Millennial Da'wa - Latifah, Nasihatul; Huriyah, Lilik; Rufqot, Nuwailah R.; Zilfa, Rohil (Proceedings of International Conference on Da'wa and Communication, 2020)
The purpose of this research is to describe the da’wa profile of Ustadz Hanan Attaki, the values ​​of character education in the da’wa material of Ustadz Hanan Attaki's millennial da’wa, and the advantages and disadvantages of Ustadz Hanan Attaki's millennial da’wa. This research is a qualitative content analysis research. The unit of analysis in this study were three videos of Ustadz Hanan Attaki's lecture uploaded on the YouTube shift channel with the title Beautiful morals of Rasulullah, the Hijrah TV channel with the title Learning Morals from the Prophet Muhammad, and the YouTube channel Salamulqolbi Channel with the title High Morals of Rasulullah saw. The results of this study state that the da’wa of Ustadz Hanan Attaki is a mission that serves to create millennials with digital media. The values ​​of character education in the millennial da’wa of Ustadz Hanan Attaki are character education for honesty, tolerance, respect, courtesy, responsibility, leadership, and fairness. The advantages of the da’wa of Ustadz Hanan Attaki are that the language and terms used are very close and suitable for the millennial generation, the material for da’wa is delivered in a relaxed and flexible way, and the da’wa media of Ustadz Hanan Attaki can be accessed very easily. While the weakness is that some of the terms used are rather difficult to be translated by the old generation.